Family Support in The Implementation of the Visit of Toddlers - Anis Auliyah; Hanik Machfudloh (Universitas Muhammadiyah Sidoarjo, 2021)
Toddler visits to posyandu are toddlers who come to posyandu to get health services such as weighing, immunization and others. Based on a preliminary survey of toddler visits at Posyandu IV, Magersari Village, it was found that 62.5% (5 out of 8) did not regularly go to the posyandu. The research design used descriptive method. The population is all respondents who have toddlers aged 12-60 months in Posyandu II, Modong Village, Tulangan Sidoarjo District as many as 15 mothers of toddlers and all of them are used as research subjects. The data are presented in the form of frequency tables, cross tabulations and analyzed descriptively without statistical tests. The results showed that most (60%) family support did not fully support and showed that most (53.3%) visits to the Posyandu were non-routine. full (11.1%). The conclusion of the study is that the visits of children under five to the posyandu that are routinely fully supported are not fully supported.